KECERDASAN NATURALIS ANAK USIA DINI DILIHAT DARI PERILAKU EKSPLORASI LINGKUNGAN DIKOMPLEK TPB SUNGAILIAT, KABUPATEN BANGKA - Mawaddah, Elsy; Husin, Azizah; Helmi, Henny; Ardi Saputra (STKIP Subang, 2026)
Naturalistic intelligence in early childhood refers to the ability to recognize and understand the natural environment. This study aims to describe children's naturalistic intelligence based on environmental exploration behavior in Taman Pesona Bangka Housing Area, Sungailiat District, Bangka Regency. The study used a descriptive quantitative approach with 30 children aged 3–7 years as the sample. Data were collected through observation and analyzed using descriptive statistics. The results show that environmental exploration behavior is in the high category, while naturalistic intelligence ranges from moderate to high.